Anxiety during the pandemic: existential grounds and ways of coping - A. A. Bakanova (Вестник университета)
The article reveals one of the psychological mechanisms of anxiety formation in response to existential challenges of uncertainty.   The purpose of the study is to describe the psychological content of anxiety during the pandemic.   The research method was the author’s questionnaire aimed at studying anxiety experience peculiarities and ways of coping with it in adults in the situation of COVID-19 pandemic. To realize the goal, adults (n = 181) aged 18 to 74 years were asked to describe their thoughts about the pandemic that cause anxiety, negative and positive perceptions of themselves in the context of the pandemic, and ways of coping with anxiety. The study results showed that anxiety in the pandemic situation has universal existential underpinnings such as fear of death, loneliness, and restriction of freedom. Anxiety is formed around two main negative perceptions of the person about themselves: “I am anxious” and “I am bad and weak”, which reflects the experience of their own vulnerability, the main causes of which are the fear of death of loved ones and experience of their own incompetence in a situation of uncertainty. To reduce anxiety during the pandemic, adults use both universal methods (mainly self-regulation methods) and conditionally specific ones related to the source of anxiety and, consequently, negative self-image. The interrelation among self-image, anxiety and ways of coping with it shows the psychological help directions within the framework of both cognitive and existential-humanistic approaches.